Receptor-mediated Endocytosis in the Caenorhabditis elegans Oocyte - Grant, Barth (The American Society for Cell Biology, 1999)
The Caenorhabditis elegans oocyte is a highly amenable system for forward and reverse genetic analysis of receptor-mediated endocytosis. We describe the use of transgenic strains expressing a vitellogenin::green fluorescent protein (YP170::GFP) fusion to monitor yolk endocytosis by the C. elegans oocyte in vivo. This YP170::GFP reporter was used to assay the functions of C. elegans predicted proteins homologous to vertebrate endocytosis factors using RNA-mediated interference. We show that the basic components and pathways of endocytic trafficking are conserved between C. elegans and vertebrates, and that this system can be used to test the endocytic functions of any new gene. We also used the YP170::GFP assay to identify rme (receptor-mediated endocytosis) mutants. We describe a new member of the low-density lipoprotein receptor superfamily, RME-2, identified in our screens for endocytosis defective mutants. We show that RME-2 is the C. elegans yolk receptor.